Using Revised Bloom's Taxonomy to Evaluate the Cognitive Levels of Questions in Indonesian High School Physics Textbooks - Aprillia, Aprillia; Qadar, Riskan; Efwinda, Shelly (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to determine the cognitive level and dimensions of knowledge about the types of Lower Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), and Higher Order Thinking Skills (HOTS) in class X high school physics textbooks on impulse momentum based on bloom taxonomy revision. We used a descriptive approach with a quantitative approach. The subjects of this research were three high school physics textbooks for class X from three different publishers and data collection techniques using analysis sheets. The research results on the LOTS category of the three open books do not contain this question category. In the MOTS category, the analysis results included 1) C2-Conceptual 10% book publishers, 70% C3-Procedural, 2) C2-Conceptual book publishers 23.1%, C3-Procedural 46.2%, 3) book publishers 3 C2-Conceptual 55.7%, C3-Procedural 42.9%. In the HOTS category, the analysis results included 1) 20% for publisher 1 C4-Procedural, 2) 30.7% for publisher 2 C4-Procedural, and 3) 42.9% for publisher 3 C4-Procedural. Category questions C5 and C6 are separate from the three textbooks.